Crystal structure of l‐rhamnose 1‐dehydrogenase involved in the nonphosphorylative pathway of l‐rhamnose metabolism in bacteria. Issue 5 (5th February 2021) - Yoshiwara, Kentaroh; Watanabe, Seiya; Watanabe, Yasunori
Abstract : Several microorganisms can utilize l ‐rhamnose as a carbon and energy source through the nonphosphorylative metabolic pathway, in which l ‐rhamnose 1‐dehydrogenase (RhaDH) catalyzes the NAD(P) + ‐dependent oxidization of l ‐rhamnose to l ‐rhamnono‐1, 4‐lactone. We herein investigated the crystal structures of RhaDH from Azotobacter vinelandii in ligand‐free, NAD + ‐bound, NADP + ‐bound, and l ‐rhamnose‐ and NAD + ‐bound forms at 1.9, 2.1, 2.4, and 1.6 Å resolution, respectively. The significant interactions with the 2′‐phosphate group of NADP +, but not the 2′‐hydroxyl group of NAD +, were consistent with a preference for NADP + over NAD + . The C5‐OH and C6‐methyl groups of l ‐rhamnose were recognized by specific residues of RhaDH through hydrogen bonds and hydrophobic contact, respectively, which contribute to the different substrate specificities from other aldose 1‐dehydrogenases in the short‐chain dehydrogenase/reductase superfamily. Abstract :